Bio-nanocomposite Photoelectrode Composed of the BacteriaPhotosynthetic Reaction Center Entrapped on a NanocrystallineTiO2 Matrix - Jilie Kong (Sensors, 2005)
A new kind of bio-nanocomposite photoelectrode was fabricated through directimmobilization of the bacterial photosynthetic reaction center (RC) proteins on ananocrystalline TiO2 matrix prepared by anodic electrodeposition. The near-infrared (NIR)-visible absorption and fluorescence emission spectra displayed that structure and activity ofthe RC remained unaltered on the nano-TiO2 film surface. High efficient light-harvesting ofthe NIR light energy by RC contributed to the distinct enhancement of the photoelectricconversion on such nanoporous matrix, which would provide a new strategy to developversatile biomimic energy convertors or photoelectric sensors.